(3CNUQ GdeNJUQGJs - (3GHf HdHGf, eMeO Hf HOQ GdOjf Hf YHO GdbGOQ, J (B1083 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Gdeabg ef TGA ef Ndbg aj GdOjf hHYO abO SfM HNdOj Cf CNJUQ cJGHj GdeSei HcGaj GdeHJOj GdcGjf aj abg GdEeGe CMeO Hf eMeO Hf MfHd hSejJg CNUQ GdeNJUQGJ s
(3BNQgG (B:s
(3ePci hSdN hcSQ Yfb bHd Rghb hfaN dMe dHjY hSf JhLjgg Edi GdbHdI Ydi Tbg GdCjSQ hhab Hg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 51s
(3eYLe GdeDdajf (B3 / 160s
(3NdGUI GdCKQ (B3 / 401s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs